Why they say “Adiós”: a critical understanding the political economy of contemporary migration of venezuelans - ÖKTEN, NİLAY (My University, 2022)
The aim of this study is to create a pattern by looking at the historical background of the migration movement in Venezuela and to reveal that the Venezuelan diaspora is a social movement that takes place with push factors, based on the push and pull theory. In this context, it has been focused on the economic and political background of the Venezuelan migration movement, and by looking at the political economy history, it has been determined that the migration movement took place in three different waves. By analyzing the push factors, the development of the migration phenomenon in Venezuela was followed and a framework was drawn with the sociological contexts of the target countries. The main argument of the article is the claim that the current Venezuelan migration movement took place with push factors, considering the economic and political conditions, while the first two migration waves were depending on the pull factors

O objetivo deste estudo é criar um padrão olhando para o contexto histórico do movimento migratório na Venezuela e revelar que a diáspora venezuelana é um movimento social que ocorre com fatores push, com base na teoria push and pull. Nesse contexto, concentrou-se no contexto econômico e político do movimento migratório venezuelano e, analisando a história da economia política, determinou-se que o movimento migratório ocorreu em três ondas diferentes. Ao analisar os fatores de impulso, acompanhou-se o desenvolvimento do fenômeno migratório na Venezuela e traçou-se um quadro com os contextos sociológicos dos países-alvo. O principal argumento do artigo é a afirmação de que o atual movimento migratório venezuelano ocorreu com fatores de impulso, considerando as condições econômicas e políticas, enquanto as duas primeiras ondas migratórias foram dependentes dos fatores de atração.

El objetivo de este estudio es crear un patrón al observar los antecedentes históricos del movimiento migratorio en Venezuela y revelar que la diáspora venezolana es un movimiento social que se lleva a cabo con factores de empuje, basados en la teoría de empujar y tirar. En este contexto, se ha centrado en los antecedentes económicos y políticos del movimiento migratorio venezolano y, al observar la historia de la economía política, se ha determinado que el movimiento migratorio se dio en tres oleadas diferentes. Mediante el análisis de los factores de empuje, se siguió el desarrollo del fenómeno migratorio en Venezuela y se trazó un marco con los contextos sociológicos de los países objetivo. El argumento principal del artículo es la afirmación de que el movimiento migratorio venezolano actual se dio con factores de empuje, considerando las condiciones económicas y políticas, mientras que las dos primeras olas migratorias dependieron de los factores de atracción.
Por que dizem “Adiós”: uma compreensão crítica da economia política da migração contemporânea de venezuelanos
Por qué dicen “Adiós”: una comprensión crítica de la economía política de la migración contemporánea de venezolanos
Keywords: Sosyal ve Beşeri Bilimler; Social Sciences and Humanities; Sosyal Bilimler (SOC); Social Sciences (SOC); Venezuela; Migration; Political economy; Push and pull theory; Economic crisis; Migração; Economia política; Teoria push and pull; Crise econômica; Migración; Economía política; Teoría push and pull; Crisis económica